Compositions of chromite, associated minerals, and parental magmas of podiform chromite deposits: The role of slab contamination of asthenospheric melts in suprasubduction zone environments - Zhou, Mei-Fu; Robinson, Paul T.; Su, Ben-Xun; Gao, Jian-Feng; Li, Jian-Wei; Yang, Jing-Sui; Malpas, John (Gondwana research, 2014)
Podiform chromitites in the mantle sections of ophiolites belong to either high-Cr (metallurgical) or high-Al (refractory) varieties. Their highly variable compositions are reflected by different Cr#s [100Cr/(Cr+Al)] and Cr2O3 and Al2O3 contents of the chromite, falling in the boninitic and MORB fields, respectively. Parental magmas of high-Cr chromitites have higher Sc, Mn, Co and Ni, and lower Ti, V, Zn and Ga concentrations than MORB melts; their trace-element patterns are similar to those of boninites, except for Ni and Zn. In contrast, high-Al chromitites have parental magmas characterized by generally flat MORB-normalized patterns, showing slight enrichments in V, Mn and Co, and depletion in Ni and Zn. Regardless of their compositions, both types of chromitites have chondrite-normalized platinum group element (PGE) patterns showing enrichment in IPGE and depletion in PPGE. A variety of platinum group minerals are typically present in both types, occurring either as euhedral inclusions or along fractures in chromite grains. These minerals have a wide span of Re–Os isotopic compositions, reflecting a variety of origins. There is a diversity of unusual minerals and mineral inclusions associated with podiform chromitites. The presence of these minerals suggest that grains of amphibolite (plagioclase, amphibole and zircon) and eclogite (coesite, kyanite and garnet) were present in the magmas from which chromite crystallized. Multiphase mineral inclusions demonstrate that podiform chromitites form from hydrous mafic magmas in suprasubduction zone environments (SSZ). We propose a new model in which chromitite formation was involved in intra-oceanic subduction zones initiated in closing oceanic basins. Continued subduction carries oceanic and possibly continental crustal materials to deep levels where they are metamorphosed under greenschist, amphibolite and eclogite facies conditions. The tearing and breakoff of the subducted slab, possibly along the transitional contact between amphibolites and eclogites, create a slab window through which the underlying asthenosphere rises and melts to generate Cr-rich mafic magmas. These upward-migrating magmas pass through the subduction zone and assimilate the subducted slab. As a result of slab contamination, these magmas become more siliceous, more oxidized and more hydrous, rapidly triggering chromite crystallization. Minute grains of chromite are suspended in the upward-moving magmas as they migrate through the overlying metasomatized mantle wedge. Such chromite-bearing magmas eventually deposit chromite in magma conduits in the uppermost mantle close to the Moho where the upward flow changes from vertical to subhorizontal and velocity is greatly reduced. Highly reduced and ultrahigh pressure minerals including diamonds are reported in literature both in podiform chromitites and host peridotites of ophiolites. Some of these minerals in association with host peridotites may have been brought by the uprising asthenosphere at mid-oceanic ridges due to the mantle convection. It is also possible that some diamonds may have formed in the subducted slab below about 150km. Some minerals of subducted slabs are preserved because they are encapsulated in chromite grains where they are protected from the SSZ melts. Some of these SSZ mantle wedges are emplaced on land to become podiform chromitite-bearing ophiolites. [Display omitted] •Podiform chromitites crystallize from hydrous and high-Mg SSZ melts.•Crustal minerals suggest crystallization of chromite after slab assimination.•Asthenospheric melts pass through slab window.•Chromite deposits in mini-magma conduits near Moho.